2001
DOI: 10.1159/000050635
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of p53, p21/WAF1, Bcl-2, Bax, Bak and Ki-67 Immunoreactivity in pT1 G3 Urothelial Bladder Carcinomas

Abstract: pT1 G3 bladder carcinomas are heterogeneous with respect to tumor recurrence and progression. Whereas some urologists treat these carcinomas by repeated transurethral resections often followed by intravesical chemotherapy or BCG instillation, others recommend cystectomy after tumor recurrence or early cystectomy after the initial diagnosis. Our goal was to determine the prognostic value of p53, p21/WAF1, Bcl-2, Bax, Bak, and Ki-67 immunoreactivity in these tumors. There were 30 patients with a new histopatholo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
22
0
6

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 47 publications
1
22
0
6
Order By: Relevance
“…Alteration of the gene (mutation or/and deletion) or protein accumulation occurs in over 50% of the cases. 26 In the present series, overexpression of p53 was seen in 61% of the tumours. In previous series of endometrial carcinoma, the reported rate is quite variable (15-77%), which may reflect the lack of consensus of the scoring methods among the studies.…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…Alteration of the gene (mutation or/and deletion) or protein accumulation occurs in over 50% of the cases. 26 In the present series, overexpression of p53 was seen in 61% of the tumours. In previous series of endometrial carcinoma, the reported rate is quite variable (15-77%), which may reflect the lack of consensus of the scoring methods among the studies.…”
Section: Discussionsupporting
confidence: 51%
“…Recent data on p53 and Ki-67, which are involved in these processes, have merged as valuable prognostic tools. 26 p53 tumour suppressor gene (17p13) encodes a nuclear phosphoprotein that controls the progression of the cell cycle, as well as apoptosis. Alteration either by mutation or/and deletion, leading to intranuclear protein accumulation in the vast majority of the cases, has been detected in over 50% of tumours.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The relevance of p53 in muscle-invasive, pT1 G3 bladder tumours is well documented, but the prognostic impact of p53 alterations in superficial, low-grade tumours remains uncertain (Friedrich et al, 2001;Wolf et al, 2001). Although some groups have shown that p53 is a significant predictor of bladder tumour progression (Schmitz-Dräger et al, 2000), others have concluded that it provides no prognostic information (Gontero et al, 2000;Friedrich et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…For some authors, p53 overexpression in the urine could aid in predicting prognosis and in identifying cases that are likely to progress from superficial to invasive disease (Wolf et al, 2001).…”
mentioning
confidence: 99%